Mesiodens and a supernumerary tooth as a cause of disorders in the eruption of teeth 21 and 22 - a case report - Małgorzata Pinkowska-Prasal; Jolanta Bialkowska-Glowacka; Monika Ratajek-Gruda; Anna Janas-Naze (Kazimierz Wielki University, 2018)
The article presents a case of surgical treatment of an 11 y.o. boy, who was diagnosed with a mesiodens and a supernumerary impacted tooth at the same time.